m6A epigenetic signature in necrotizing enterocolitis: insights from murine to neonatal studies - Chen, Yixian; Wei, Qiaozhen; Gan, Yuan; Wei, Ba; Huang, Qingmei; Pan, Shuangjing; Chen, Yujun (Frontiers in Immunology, 2026)
Necrotizing enterocolitis (NEC) is a severe intestinal infectious disease. m6A modification plays a critical role in intestinal homeostasis and infection, while its role in NEC remains unclear. This study aimed to investigate the landscape of m6A modifications in NEC, spanning from animal models to humans. This study aimed to investigate the landscape of m6A modifications in NEC, spanning from animal models to humans. In our study, m6A was widely distributed in ileal tissues, with elevated global m6A levels detected via dot blot and immunohistochemistry. qRT-PCR and western blot assays revealed increased expression of METTL3 and METTL14 in NEC mice. Subsequently, RNA-seq and MeRIP-seq were performed on ileal samples from NEC infants and controls. RNA-seq identified 2,108 differentially expressed genes (DEGs), while MeRIP-seq detected 19,242 m6A peaks in NEC and 16,318 peaks in controls, with 8,957 differential peaks. Integrative analysis of RNA-seq and MeRIP-seq datasets identified differentially m6A-modified DEGs, which were associated with leukocyte migration, adhesion, and predominantly enriched in cytokine-cytokine receptor interactions. Notably, 363 genes exhibited concurrent m6A hypermethylation and transcriptional upregulation in NEC infants, with significant enrichment in the NF-κB signaling pathway. 192 genes displayed m6A hypermethylation accompanied by transcriptional downregulation, showing significant enrichment in focal adhesion and ECM-receptor interaction pathways. This study pioneers the systematic characterization of m6A methylation patterns in NEC, offering novel insights into m6A-mediated molecular mechanisms driving NEC pathogenesis.